Structural evolution across the metal-insulator transition of strongly distorted Lu1−xScxNiO3 perovskites (x = 0, 0.1, 0.2). (2nd December 2020) - Cui, Qi; Wang, Ningning; Alonso, Jose A; Fauth, François; Cheng, Jinguang
Abstract: RNiO3 perovskites have been described to present thermally driven metal-insulator transitions (at TMI ) as a function of the rare-earth ion size (R = Pr to Lu). Aiming to extend the stability range of RNiO3 for smaller R 3+ ions, we prepared Lu1−x Scx NiO3 (x = 0, 0.1, 0.2) perovskites, being Sc 3+ ions substantially smaller than Lu 3+, by using a multi-anvil high-pressure synthesis device at 10 GPa. We have studied the structural evolution of Lu0.9 Sc0.1 NiO3 by synchrotron x-ray diffraction (SXRD) from room temperature to 350 °C. The symmetry of the lattice evolves from monoclinic ( P2 1 /n ) to orthorhombic ( Pbnm ) upon heating across TMI (≈320 °C), with the existence of two chemically and crystallographically distinct nickel sites in the insulating, monoclinic regime, whereas the metallic phase has a single NiO6 environment. A simultaneous structural and electronic transition implies an abrupt evolution of the lattice parameters and size of the NiO6 octahedra upon entering the metallic regime, leading to the merging of the disproportionated Ni-O bond lengths. The magnetic properties correspond to the establishment of antiferromagnetic correlations at the Ni sublattice; a decrease of the TN ordering temperature from 122 K (x = 0) to 113 K (x = 0.2) is observed as the Sc content increases, which is concomitant with a more distorted perovskite structure.